Antibiofilm agent pterostilbene is able to enhance antibiotics action against Staphylococcus epidermidis. (March 2021) - Kašparová, P.; Vaňková, E.; Brázdová, L.; Lokočová, K.; Maťátková, O.; Masák, J.
Abstract: Pterostilbene (PTE) is a naturally occurring compound originally isolated from Pterocarpus spp. It has been widely used in traditional Indian medicine and later discovered to have various beneficial pharmacological effects such as antioxidant properties, hypoglycaemic or antitumor, and antimicrobial activity. This work is focused on demonstrating PTE synergistic effect with erythromycin and tetracycline to reduce their needed effective concentration for suppression of Staphylococcus epidermidis planktonic cells growth and biofilm formation. The secondary aim is to find these combinations effect on the production of its virulence factors. PTE was found to be effective in inhibition of its planktonic cells with MIC80 values 25–37.5 mg l −1 . Simultaneously, it decreased the metabolic activity of biofilm cells and was especially effective on a clinical isolate (MBIC80  = 35 mg l −1 ) in contrast to the conventional antibiotics. In combination, PTE helped the antibiotics to overcome the tolerance of S. epidermidis biofilm cells (5 mg l −1 of each antibiotic with 49 mg l −1  PTE caused more than 85% inhibition of metabolic activity). It permeabilized cytoplasmic membrane of S. epidermidis cells and altered their surface hydrophobicity. Therefore, PTE has a great potential to enhance antibiotics action in the treatment of infections caused by this pathogen. Graphical abstract: Image 1 Highlights: Pterostilbene has antimicrobial and antibiofilm effect on Staphylococcus epidermidis . Its combinatory effect with antibiotics was observed. It enhanced erythromycin or tetracycline action likely via membrane permeabilization. Biofilm formation was not inhibited by erythromycin or tetracycline up to 400 mg l −1 5 mg l −1 of each antibiotic with pterostilbene (32.5 mg l −1 ) resulted in 80% inhibition.